Cyclin D1b Splice Variant Promotes αvβ3-mediated EMT Induced by LPS in Breast Cancer Cells - Luo, Bao-ping; Luo, Jing; Hu, Yi-bing; Yao, Xiao-wei; Wu, Feng-hua (Current medical science, 2018)
Summary Epithelial-to-mesenchymal transition (EMT) plays a critical role in cancer metastasis, and is relevant to the inflammatory microenvironment. Lipopolysaccharide (LPS), a cell wall constituent of gram-negative bacteria, has been reported to induce EMT of cancer cells through TLR4 signal. We previously reported that LPS promoted metastasis of mesenchymallike breast cancer cells with high expression of cyclin D1b. However, the role of cyclin D1b in LPS-induced EMT has not been fully elucidated. In the present study, we described that cyclin D1b augmented EMT induced by LPS in MCF-7 breast cancer cells. Cyclin D1b markedly amplified integrin αvβ3 expression, which was further up-regulated under LPS stimulation. Our results showed ectopic expression of cyclin D1b promoted invasiveness of epithelial-like MCF-7 cells under LPS stimulation. Additionally, LPS-induced metastasis and EMT in MCF-7-D1b cells might depend on αvβ3 expression. Further exploration indicated that cyclin D1b cooperated with HoxD3, a transcription factor promoting αvβ3 expression, to promote LPSinduced EMT. Knockout of HoxD3 repressed LPS-induced EMT and αvβ3 over-expression in MCF-7 cells with high expression of cyclin D1b. Specifically, all these effects were in a cyclin Dla independent manner. Taken all together, LPS up-regulated integrin αvβ3 expression in MCF-7 cells with high expression of cyclin D1b and induced EMT in breast cancer cells, which highlights that cyclin D1b may act as an endogenous pathway participating in exogenous signal inducing EMT in breast cancer cells.